WHOLE-BODY VIBRATION EXERCISE IS WELL TOLERATED IN PATIENTS WITH DUCHENNE MUSCULAR DYSTROPHY: A SYSTEMATIC REVIEW - Moreira-Marconi, Eloá; Sá-Caputo, Danubia C; Dionello, Carla F; Guedes-Aguiar, Eliane O; Sousa-Gonçalves, Cintia R; Morel, Danielle S; Paineiras-Domingos, Laisa L; Souza, Patricia L; Kütter, Cristiane R; Costa-Cavalcanti, Rebeca G; Costa, Glenda; Paiva, Patricia C; et al. (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: Duchenne muscular dystrophy (DMD) is caused by a defective gene located on the X-chromosome,responsible for the production of the dystrophin protein. Complications in the musculoskeletal system have beenpreviously described in DMD patients. Whole body vibration exercise (WBVE) is a treatment that improvesmusculoskeletal function in movement disorders. The aim of this study was to review the effects of WBVE onfunctional mobility, bone and muscle in DMD patients.Materials and Methods: Four databases were searched. Three eligible studies were found; all three conclude themanagement of DMD patients with WBV was clinically well tolerated. The studies used a side-alternating WBVsystem, frequencies 7 - 24 Hz; and amplitudes 2 - 4 mm.Results: A work indicates that a temporary increase in creatine kinase in DMD during the first days of WBV wasobserved, but other authors did not find changes. No significant changes in bone mass, muscle strength or bonemarkers. Some patients reported subjective functional improvement during training. Interpretation:Conclusion: It is concluded that WBV seems to be a feasible and well tolerated exercise modality in DMD patients.